Pengembangan Prototipe Sistem S.K.P.I. untuk Pendamping Ijazah Berbasis Google Suite - Nuraini Febrianti; Hasna Alaurrahman; Amalia Rahmah (LPPM STT Terpadu Nurul Fikri, 2023)
Diploma Supplement is a document containing information about fulfilling college graduates' competencies. The existence of the Merdeka Learning-Independence Campus (MBKM) program encourages students to acquire valuable competencies so that a portfolio of abilities and experiences can be accommodated in the Diploma Supplement. In this research, the Nurul Fikri Integrated Technology College still needs to implement Diploma Supplement because no procedures and information systems support Diploma Supplement management. Therefore, researchers will develop a prototype of the Diploma Supplement system for a Google Suite-based diploma companion that is comprehensive and can make it easier for the academic community. This research methodology uses the Scrum framework method. The entire work process for Diploma Supplement utilizes Google Suite, especially Google Drive, Google Docs, Google Forms, and Google Sheets with the AutoCrat add-on. This research successfully developed a prototype of the Diploma Supplement system for a Google Suite-based diploma companion. The results of this study can make it easier for students to process Diploma Supplement submissions because it is done online, BAAK also does not need to make Diploma Supplement manually because the system is already integrated, and campuses can save costs for creating, managing, and maintaining the system.